Pengaruh Bauran Pemasaran Terhadap Loyalitas Konsumen yang Dimediasi oleh Kepuasan Konsumen Les Privat Be Smart Student (Studi Kasus: Yayasan Pendidikan Ruang Ilmu Cikarang) - Putri Ismawati; Hervina Puspita Darmayanti; Yati Sulastri; Dimas Bayu Prasetyo; Anna Wulandari (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
The marketing mix is a set of controllable tactical marketing tools that companies combine to generate desired responses in their target markets. The main objective of this study is to examine the influence of the marketing mix on customer satisfaction, the impact of the marketing mix on customer loyalty, and the role of customer satisfaction in mediating the relationship between the marketing mix and customer loyalty. This research employs a quantitative method, involving customer loyalty as the dependent variable, the marketing mix as the independent variable, and customer satisfaction as the mediating variable. The results of the study indicate that the marketing mix has a significant impact on customer satisfaction, meaning that the better the marketing mix, the higher the level of customer satisfaction. Furthermore, the marketing mix also significantly influences customer loyalty, indicating that a higher quality marketing mix leads to increased customer loyalty. Regarding the mediating variable, it is concluded that customer satisfaction serves as a mediator linking the marketing mix and customer loyalty, demonstrating that customer satisfaction effectively bridges the relationship between the marketing mix and customer loyalty.